A Role for Monomethylation of Histone H3-K27 in Gene Activity in Drosophila. Issue 3 (1st March 2018) - Wang, Liangjun; Joshi, Preeti; Miller, Ellen L; Higgins, LeeAnn; Slattery, Matthew; Simon, Jeffrey A
Abstract: N-terminal histone tails emanate from the chromatin fiber—providing docking surfaces for regulatory proteins—and are commonly modified by lysine methylation... Polycomb repressive complex 2 (PRC2) is a conserved chromatin-modifying enzyme that methylates histone H3 on lysine-27 (K27). PRC2 can add one, two, or three methyl groups and the fully methylated product, H3-K27me3, is a hallmark of Polycomb-silenced chromatin. Less is known about functions of K27me1 and K27me2 and the dynamics of flux through these states. These modifications could serve mainly as intermediates to produce K27me3 or they could each convey distinct epigenetic information. To investigate this, we engineered a variant of Drosophila melanogaster PRC2 which is converted into a monomethyltransferase. A single substitution, F738Y, in the lysine-substrate binding pocket of the catalytic subunit, E(Z), creates an enzyme that retains robust K27 monomethylation but dramatically reduced di- and trimethylation. Overexpression of E(Z)-F738Y in fly cells triggers desilencing of Polycomb target genes significantly more than comparable overexpression of catalytically deficient E(Z), suggesting that H3-K27me1 contributes positively to gene activity. Consistent with this, normal genomic distribution of H3-K27me1 is enriched on actively transcribed Drosophila genes, with localization overlapping the active H3-K36me2/3 chromatin marks. Thus, distinct K27 methylation states link to either repression or activation depending upon the number of added methyl groups. If so, then H3-K27me1 deposition may involve alternative methyltransferases beyond PRC2, which is primarily repressive. Indeed, assays on fly embryos with PRC2 genetically inactivated, and on fly cells with PRC2 chemically inhibited, show that substantial H3-K27me1 accumulates independently of PRC2. These findings imply distinct roles for K27me1 vs. K27me3 in transcriptional control and an expanded machinery for methylating H3-K27.